Ground-based observation of shortwave solar radiation during solar eclipse on october 3, 2005 in Chisinau, Moldova - Aculinin, Alexandr (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2006)
The influence of partial annular solar eclipse observed during October 3, 2005 onto the